2014
DOI: 10.1128/genomea.01247-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Porcine Parvovirus Strain Isolated in Central China

Abstract: We report here the complete genome sequence of the porcine parvovirus (PPV) strain J-PPV, isolated from central China. Our data, together with sequence data for PPV isolates from other regions of China, will help in understanding the epidemiology and molecular characteristics of PPV field isolates in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Phylogenetic analysis showed that the JY strain was the first German-like PPV isolate discovered in China ( Hao et al., 2011 ). More reports indicate that isolated strains, such as PPV2010, J-PPV, and GD2013, have the characteristics of becoming vaccine strains ( Cui et al., 2012 ; Deng et al., 2020 ; Wang et al., 2014 ). The BQ strain isolated in 2005 has been developed by our laboratory into an inactivated vaccine that is not yet on the market ( Shangjin et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis showed that the JY strain was the first German-like PPV isolate discovered in China ( Hao et al., 2011 ). More reports indicate that isolated strains, such as PPV2010, J-PPV, and GD2013, have the characteristics of becoming vaccine strains ( Cui et al., 2012 ; Deng et al., 2020 ; Wang et al., 2014 ). The BQ strain isolated in 2005 has been developed by our laboratory into an inactivated vaccine that is not yet on the market ( Shangjin et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%